Design and study of psychometric properties of the Community Attitude to Abortion Scale (CAAS) with the Chilean population: Autonomy and Stigma - Pérez Sánchez, Beatriz; Burgos Padilla, Juan José; Alveal-Álamos, Carolina; Concha-Salgado, Andrés; Jara Sepúlveda, Luisa; Rodríguez Díaz, Francisco Javier (Frontiers in Psychology, 2022)
Attitudes towards abortion are related to structural, cultural, and direct gender-based violence. This violence can affect women’s mental, physical and reproductive health. Therefore, it is essential to know the nature of community attitudes towards abortion. Since we currently do not have an instrument that measures attitudes towards abortion in Chile, we set the objective of this study to design the Community Attitude to Abortion Scale (CAAS) and analyze its psychometric properties in a Chilean community population. Using probabilistic sampling stratified by geographic macrozone, we obtained a sample of 1,223 participants with a mean age of 36.7 years (SD = 13.56). As a result, we obtained a scale of 18 items and two correlated factors, Autonomy and Stigma. This structure fits better as an ESEM model. In addition, we obtained evidence of concurrent and discriminant validity: The scores on the factors of the Universal Religious Involvement Scale (I-E12) correlated negatively with Autonomy and positively with Stigma; participants with low levels of identification with a right-wing political orientation, with high levels of identification with a left-wing, pro-feminist, pro-LGBTQ +, and pro-euthanasia political orientation, obtained higher mean scores on Autonomy, and lower on Stigma. The results and implications are discussed.